Enrollment attrition at Coronado's School of Quezon City : basis for school recovery plan - Coronado, Joel M. (Manila : National University, 2023)
Technology innovation and its use have revolutionized education over the pastdecade, changing the foundation for learning. The new normal requires a re-calibration, which should be done. Every school administrator should keep in mind the factors on which all private schools should focus and concentrate in terms of methods, strategies, approaches, learning skills, and enrollment activities that will increase the number of learners who join every academic institution's learning community.
Title Page -- Approval Sheet -- Table of Contents -- Dedication -- Acknowledgements -- Abstract -- Chapter 1. Introduction -- Chapter 2. Literature Review -- Chapter 3. Methodology -- Chapter 4. Results and Discussion -- Chapter 5. Summary, Conclusion, and Recommendations -- References -- Appendices.
Includes bibliographical references.